Budaya Mutu dan Keberlanjutan Kinerja : Sebuah Pendekatan Manajerial Modern - Imam Fatkhullah; Shofam Amim Mujadid; Tegar Efrizal; Nuriyah Nuriyah (Jurnal Kewirausahaan Cerdas dan Digital, 2025)
In the context of modern organizations, performance can no longer be measured solely through short-term target achievements. A strong foundation of quality culture is required to ensure sustainable performance. This study aims to examine the relationship between quality culture and organizational performance sustainability through a modern managerial approach. The method used is descriptive qualitative, employing literature studies and conceptual analysis of theories related to quality management, organizational culture, and performance sustainability. The findings indicate that quality culture holds a strategic role in shaping work behavior, strengthening management systems, and fostering continuous innovation. The application of quality values—such as commitment to continuous improvement, customer orientation, and consistency in process control—contributes to the creation of a productive work environment that is responsive to change. Integrating quality culture into all aspects of the organization also enhances operational efficiency, reinforces teamwork, and promotes data-driven decision-making. These aspects lead to greater performance consistency, improved customer satisfaction, and long-term competitive advantage. Therefore, quality culture does not merely serve as a behavioral guideline but becomes a fundamental pillar in building an adaptive, innovative, and sustainable organization capable of navigating an increasingly complex business environment.